Calculation of the Budget Plan for the ASN 2 Apartment Building Construction Project - Pratama, Rinata Candra; Ghassani, Dewi Bussaina; Rahayu, Umi (International Journal of Education, Information Technology, and Others, 2025)
Construction project for the development of apartment buildings for the State Civil Apparatus (ASN2) is located in North Penajam Paser Regency and Kutai Kartanegara Regency, the main location of the National Capital City (IKN) in Sepaku, North Penajam Paser, which plays an important role in infrastructure development and connectivity. The location of the ASN 2 apartment complex project in Sepaku Village, North Penajam Paser Regency, is located at the intersection of Jl. Wonosari and Jl. Sepaku. To the north is Nusantara Hospital, to the south are Sepaku residents' homes, and to the east and west are swampy areas. The planning work for the construction of the Penajam Paser Utara ASN apartment complex uses the 2024 Volume 2 Work Unit Price Calculation (PHSP) and serves to determine the total costs required based on an analysis of the unit price for each type of work using the Volume 2 PHSP. The planning work for the construction of the Penajam Paser Utara ASN apartment building shows that the cost of installing red brick walls is cheaper than white brick walls. Wall construction using white bricks only costs Rp. 468,000. 000.00, while using red bricks requires a cost of Rp. 527,000,000.00, making the use of white brick walls more cost-efficient.